Effectiveness of Web-Based Versus Face-To-Face Delivery of Education in Prescription of Falls-Prevention Exercise to Health Professionals: Randomized Trial - Maloney, Stephen; Haas, Romi; Keating, Jennifer L; Molloy, Elizabeth; Jolly, Brian; Sims, Jane; Morgan, Prue; Haines, Terry (JMIR Publications, 2011)
BackgroundExercise is an effective intervention for the prevention of falls; however, some forms of exercises have been shown to be more effective than others. There is a need to identify effective and efficient methods for training health professionals in exercise prescription for falls prevention. ObjectiveThe objective of our study was to compare two approaches for training clinicians in prescribing exercise to prevent falls. MethodsThis study was a head-to-head randomized trial design. Participants were physiotherapists, occupational therapists, nurses, and exercise physiologists working in Victoria, Australia. Participants randomly assigned to one group received face-to-face traditional education using a 1-day seminar format with additional video and written support material. The other participants received Web-based delivery of the equivalent educational material over a 4-week period with remote tutor facilitation. Outcomes were measured across levels 1 to 3 of Kirkpatrick's hierarchy of educational outcomes, including attendance, adherence, satisfaction, knowledge, and self-reported change in practice. ResultsOf the 166 participants initially recruited, there was gradual attrition from randomization to participation in the trial (n = 67 Web-based, n = 68 face-to-face), to completion of the educational content (n = 44 Web-based, n = 50 face-to-face), to completion of the posteducation examinations (n = 43 Web-based, n = 49 face-to-face). Participant satisfaction was not significantly different between the intervention groups: mean (SD) satisfaction with content and relevance of course material was 25.73 (5.14) in the Web-based and 26.11 (5.41) in the face-to-face group; linear regression P = .75; and mean (SD) satisfaction with course facilitation and support was 11.61 (2.00) in the Web-based and 12.08 (1.54) in the face-to-face group; linear regression P = .25. Knowledge test results were comparable between the Web-based and face-to-face groups: median (interquartile range [IQR]) for the Web-based group was 90.00 (70.89-90.67) and for the face-to-face group was 80.56 (70.67-90.00); rank sum P = .07. The median (IQR) scores for the exercise assignment were also comparable: Web-based, 78.6 (68.5-85.1), and face-to-face, 78.6 (70.8-86.9); rank sum P = .61. No significant difference was identified in Kirkpatrick's hierarchy domain change in practice: mean (SD) Web-based, 21.75 (4.40), and face-to-face, 21.88 (3.24); linear regression P = .89. ConclusionWeb-based and face-to-face approaches to the delivery of education to clinicians on the subject of exercise prescription for falls prevention produced equivalent results in all of the outcome domains. Practical considerations should arguably drive choice of delivery method, which may favor Web-based provision for its ability to overcome access issues for health professionals in regional and remote settings. Trial RegistrationAustralian New Zealand Clinical Trials Registry number: ACTRN12610000135011; http://www.anzctr.org.au/ACTRN12610000135011.aspx (Archived by WebCite at http://www.webcitation.org/63MicDjPV)